Improving Students' Conceptual Understanding in Indonesian Language Learning by Utilizing Newspaper Media at MI Negeri Kayong Utara - Hendriatik; Hasni (Journal of Media and Learning Technology, 2025)
This study aims to improve student learning outcomes in Islamic religious education learning by using newspaper media. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were students of madrasah iftida'iyah. The data of this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that newspaper media can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 47.71%, the first cycle 69.39% and in the second cycle it increased to 90.66%. Thus, the use of newspaper media can be used as an alternative to improve student learning outcomes in Islamic religious education learning.